Do the Antenatal Care and Perinatal Outcomes of Women with a Vietnamese Migration Background Differ from Those of Other Women? - Lorenz-Meyer, Lisa Antonia; Sziborra, Clara; Henrich, Wolfgang; David, Matthias (Geburtshilfe und Frauenheilkunde, 2025)
In Germany, 0.25% of the total population are persons with a Vietnamese migration background. There are almost no studies on this particular group of immigrants. We compared the perinatal data of women with a Vietnamese migration background with the pregnancy outcomes of non-Vietnamese women also living in Germany.After using name analysis to allocate women into different groups, the perinatal data of women with a Vietnamese migration background who gave birth between 1.1.2016 and 31.12.2019 in Campus Charité Mitte in Berlin were retrospectively evaluated. These data were compared in a 3:1 ratio with the data of women of non-Vietnamese origin and the same age and parity. Multivariate regression analysis was used to determine factors which influenced caesarean section rates, the transfer rates of neonates to the neonatal department, and the rates of higher degree perineal tears.The perinatal data of 470 women with a Vietnamese migration background, 209 (44.5%) of whom were registered as living in a refugee shelter, were compared with those of 1410 controls. An “ideal pregnancy outcome,” which included giving birth after 37 + 0 weeks of gestation, a 5-minute Apgar score ≥ 8, arterial cord blood pH ≥ 7.20, no transfer of the newborn to the neonatal department, and spontaneous birth or vacuum extraction without a higher degree perineal tear, was recorded for 44.5% of women with and 38.1% of women without a Vietnamese migration background (p = 0.1), despite the lower attendance rates at antenatal screening appointments of Vietnamese women. Accommodation in a shelter for refugees was a protective factor against caesarean section (OR 0.5, 95% CI: 0.36–0.73) and transfer of the newborn to the neonatal department (OR 0.45, 95% CI: 0.23–0.89). A Vietnamese migration background was a risk factor for a third-degree perineal tear (OR 5.4, 95% CI: 1.4–21.30)Despite lower levels of antenatal care, women with a Vietnamese migration background did not have poorer pregnancy outcomes.In Deutschland machen Menschen mit vietnamesischem Migrationshintergrund 0,25% der Gesamtbevölkerung aus. Zu dieser besonderen Migrantinnengruppe gibt es bisher kaum Studien. Wir vergleichen Perinataldaten von Frauen mit vietnamesischem Migrationshintergrund mit den Schwangerschaftsausgängen nicht vietnamesischer Frauen.Nach einer Gruppenzuordnung mittels Namensanalyse wurden retrospektiv die Perinataldaten von Frauen mit vietnamesischem Migrationshintergrund ausgewertet, die zwischen 01.01.2016 und 31.12.2019 am Campus Mitte der Charité geboren haben. Gegenüber gestellt wurden in einem 3:1-Verhältnis Frauen nicht vietnamesischer Herkunft gleichen Alters und gleicher Parität. Durch multivariable Regression wurden Einflussfaktoren auf die Sectio- und Verlegungsrate der Neugeborenen auf die Neonatologie sowie auf die Rate an höhergradigen Dammrissen bestimmt.Die Perinataldaten von n = 470 Frauen mit vietnamesischem Migrationshintergrund, von denen n = 209 (44,5%) in einer Unterkunft für Geflüchtete gemeldet waren, wurden mit n = 1410 Kontrollpatientinnen verglichen. Ein „idealer Schwangerschaftsausgang“ mit Geburt ab 37 + 0 SSW, einem 5-Minuten-Apgar-Wert ≥ 8, einem arteriellen Nabelarterien-pH ≥ 7,20, ohne Verlegung in die Neonatologie bei Spontangeburt oder Vakuumextraktion ohne höhergradigen Dammriss lag bei 44,5% der Frauen mit und bei 38,1% der Frauen ohne vietnamesischen Migrationshintergrund vor (p = 0,1), trotz geringerer Inanspruchnahme von Vorsorgeuntersuchungen. Die Unterbringung in einer Unterkunft für Geflüchtete war ein protektiver Faktor gegen eine Sectio (OR 0,5, 95%-KI 0,36–0,73) und eine Verlegung auf die Neonatologie (OR 0,45, 95%-KI 0,23–0,89). Der vietnamesische Migrationshintergrund war ein Risikofaktor für einen Dammriss III° (OR 5,4, 95%-KI 1,4–21,30)Frauen mit vietnamesischem Migrationshintergrund weisen trotz geringerer Schwangerenvorsorge keine schlechteren Geburtsausgänge auf.
Keywords: migration; antenatal care; Vietnam; perinatal data; refugee